Islamic Work Ethics affect the employee Performance; case study of several universities in Indonesia - Abdurrahman Basalamah (Center of Economic Students Journal, 2025)
Islamic Work Ethics (IWE) play a central role in shaping organizational culture, particularly within Islamic-based higher education institutions. The integration of Islamic ethical principles such as honesty, fairness, healthy competition, and mutual assistance is expected to enhance employee performance and contribute to the achievement of institutional goals. While studies on work ethics have been widely conducted, research specifically focusing on IWE within the context of Islamic universities in Indonesia remains limited. This study aims to examine the effect of IWE on employee performance in several Islamic universities in East Java, namely Universitas Islam Malang (UNISMA), Universitas Islam Negeri (UIN), and Universitas Muhammadiyah Malang (UMM). The research employed a quantitative approach supported by qualitative insights. Data were collected through questionnaires and semi-structured interviews with permanent staff members of the three universities. The analysis revealed that IWE has a significant positive effect on employee performance. Employees who embraced values of Islamic ethics, particularly those emphasizing healthy competition and mutual help, demonstrated higher levels of productivity, discipline, and collaborative behavior. Interviews further supported these findings, with respondents acknowledging that Islamic values foster a sense of responsibility, solidarity, and motivation to contribute positively to the organization. The results confirm that IWE is an important determinant of employee performance in Islamic universities. By embedding ethical principles into workplace practices, institutions can strengthen human resource quality and align organizational goals with Islamic values. This study contributes to the growing body of literature on Islamic ethics in management and highlights the need for future research that explores broader cultural and institutional contexts. Expanding the scope of research to include different regions and employing longitudinal approaches would provide deeper insights into the long-term impact of IWE on organizational sustainability.